Drug Selective Poly (Vinyl chloride)-based Sensor of Desipramine Hydrochloride - Gupta, V.K. (2009)
The novel ion-pair ([TPB]- [DH]+) of the quaternary ammonium drug desipramine hydrochloride, 3-(5,6 dihydrobenzo[b][1]benzazepin-11-yl)-N-methylpropan-1-amine, has been synthesized and incorporated into a poly(vinyl chloride)-based membrane sensor for the quantification of desipramine hydrochloride in different pharmaceutical preparations. The influence of the membrane composition on the potentiometric responses of the membrane sensor has been found to substantially improve the performance characteristics. The best performance was reported with membranes having the composition (in mg) of ([TPB]- [DH]+) (5): PVC (150): o-NPOE (150). The proposed sensor (sensor no. 4) exhibits a nernstian response in the concentration range of 2.2 × 10-6 – 1.0 × 10-2 M with a detection limit of 1.2 × 10-6 M. The membrane sensor performs satisfactorily over the pH range of 2.8 – 7.4 with a fast response time of 12 seconds. The sensor no. 4 can tolerate a non-aqueous content of up to 20% and can be utilized for the determination of drug concentration in pharmaceutical preparation (tablets) and in body fluids such as urine and blood samples. The results were comparatively evaluated with Liquid Chromatography (LC). It was observed that the concentration of drug was greater in the blood sample than in the urine sample, as most of the drug is metabolized in the liver before discharge to urine.